PERSEPSI MASYARAKAT BEKONANG TERHADAP KEBERADAAN KOMUNITAS PUNK - Helmy, Muhammad (ISSN.2252-8407)
Muhammad Helmy, K8407036, Public Perception Of Existence Bekonang Punk Community (Case Studies in Sentul Hamlet, Village Bekonang, District Mojolaban) Thesis, Surakarta: Faculty of Teacher Training and Education, University of Surakarta of March, 2012. The research was conducted at the Sentul Hamlet, Village Bekonang, District Mojolaban because there is an interesting phenomenon. The presence of the punk community that called itself Street Punk Bekonang Riot is a phenomenon that resulted in controversy and invite the attention of the general public. Behavior punk kids often indifferent and violate societal norms resulted in a negative view of the public, although not all people feel disturbed by its presence. Based on this we conducted a study to determine how the behavior of punk kids in the community and outside the community or society. And what about public perception, community leaders and local authorities to the presence of the punk community. This study used descriptive qualitative research method. Strategies single stuck case study. Source data obtained from informants, events, locations and documents. Informants were selected, namely the general public, community Bekonang (hamlet Sentul), punk and local governments. Footage using purposive sampling technique with snowball sampling. Data collection techniques used were in-depth interviews and direct observations. The validity of the data obtained through sources triagulasi, triagulasi triagulasi method and theory. Data analysis techniques used model is interactive analysis. The results showed that (1) the punk community activities: hanging out together and drinking, playing cards, singing on the street, in the rehearsal studio band music, punk music concert both within and outside the region and make the gigs (music concert) punk itself . These activities aim to demonstrate the existence of punk in the community and change and change society's view that punk is not just scum. (2) The perception of the public towards the view that punk is a punk teenagers who have embraced a lifestyle that is incompatible with the surrounding environment that embraced freedom because punk had been mischaracterized through the child's behavior in the punk scene like hanging out while drinking, to be indifferent indifferent to the environment and ignores the prevailing norms, but they are also creative in working in the field of music. (3) The relationship punk like behavior with prevailing norms in society, namely: a) The majority of people think that punk is a negative behavior because they tend to deviate from the norm and may disturb the public tranquility, although not all people feel disturbed by the presence of the punk community . b) Although the child's behavior, including punk socially deviant behavior but not in the area of ??law violations. 3) Although punk behavior considered deviant by the majority of society, but the behavior of the child as a subject punk feel that as a punk subculture has its own norms of the dominant culture that tends so prevailing norms in society are not the same as the prevailing norms in the punk community . Keywords     : Culture, Subculture